(untitled) (CIPEEX, 2025)
The hypocaloric diet, when properly planned, has as its principle caloric restriction, and food enrichment with polyunsaturated or monounsaturated fats, inclusion of nutritious foods rich in fiber, prioritizing all types of vegetables, eggs, red fruits, legumes, coconuts, nuts, among others, offering a balanced and healthy diet following the patient’s supplementary needs. By using these low-calorie, but very nutritious foods, it makes the consumption of vegetables, fruits and beneficial items become a habit. Depression is a disease that inhibits the uptake of serotonin and norepinephrine, and affects an average of 10.4% of the Brazilian population. The objective of this abstract was to investigate the importance of a low-calorie diet in patients with depressive disorder in the literature. The inhibition caused by the disorder may be due to a low intake of foods with high nutritional value, consequently reducing the consumption of essential amino acids, responsible for the synthesis of these neurotransmitters, and may thus cause a worsening of depressive symptoms. In the pathophysiological perception, this disease is associated with obesity due to the inflammatory condition, increased oxidative stress and mitochondrial dysfunction, responding to a key point that is the direct link between the intestine and the brain. Nothing that food goes beyond the principle of survival, it is a path to pleasure through the release of neurotransmitters that have a function of providing well-being, blood pressure homeostasis, mood regulation, sleep, heart rate, sensitivity, intellectual functions, among others. An understood factor to be highlighted is the relationship of lower susceptibility to the disease when there is adequate consumption of folate, omega-3, monounsaturated fatty acids, foods such as fish, fruits, vegetables and legumes, nuts, olive oil. Seeking to associate the factors of lower susceptibility of the disorder with a diet that brought characteristics close to nutrients that were necessary to minimize the damage, he identified that the low-calorie diet presents a positive factor, going against the prioritization of antioxidative foods and focused on low caloric intake in a healthy way. Therefore, studies show great potential to administer a nutrient-rich diet that will reduce inflammation and serotonin-inhibiting cells, thus promoting not only physical improvement, but also support for psychological improvement, this diet must be accompanied by a professional so that it can extract the best desired performance without compromising or harming the patient’s health.